If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 1 = 2x(6x + 1) Multiply 2 * 1 2 = 2x(6x + 1) Reorder the terms: 2 = 2x(1 + 6x) 2 = (1 * 2x + 6x * 2x) 2 = (2x + 12x2) Solving 2 = 2x + 12x2 Solving for variable 'x'. Reorder the terms: 2 + -2x + -12x2 = 2x + -2x + 12x2 + -12x2 Combine like terms: 2x + -2x = 0 2 + -2x + -12x2 = 0 + 12x2 + -12x2 2 + -2x + -12x2 = 12x2 + -12x2 Combine like terms: 12x2 + -12x2 = 0 2 + -2x + -12x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(1 + -1x + -6x2) = 0 Factor a trinomial. 2((1 + -3x)(1 + 2x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {0.3333333333, -0.5}
| 2x+4y=44 | | 2r-14=-16 | | 3x(x)=1(4x-1) | | 12=-6(y-17) | | (5/6)=(n/15) | | (70/14)=(10/n) | | u(2u-1)=3*1 | | 3*57/15 | | (n/7)=(6/21) | | 2p-8/6p-24 | | 270.04=2r*3.14 | | 6p-42/3p-21 | | x^2-3x=18*13 | | 250+1.25=C | | 7-3(2x-5)-4x= | | 250+1.25X=C | | 7(x-5)=4x-23 | | 4x+20y=60 | | 6t^2-18t+12=0 | | 18w-10-6w=5 | | 3x+2x+3y=180findy | | 5y-18=2y*7 | | (2-9xy^2)x*dx+(4y^2-6x^3)y*dy=0 | | 3x+1=5+x | | y^2-5y+49=y+2 | | tan(27)=13/x | | (2x+2x)=35+5x | | -9x-13=-104 | | 5x+4x+6=2x+12 | | -38+10x=6x+66 | | -(x-7)=6x+8 | | 2(14-5y)-y=-5 |